Chemical and Physical Characteristics of Soils under Maize (Zea mays L.) Cultivation in Pulubala District, Gorontalo Regency - Erwan Djunaid Abukaria; Zulzain Ilahude; Fitria S. Bagu; Mahyunita Abdul Gafur; Hayatiningsih Gubali (International Journal of Technology and Education Research, 2026)
Soil fertility is a key factor influencing maize productivity, particularly in intensive agricultural areas. This study aimed to evaluate the chemical and physical soil properties of maize (Zea mays L.) fields in Pulubala District, Gorontalo Regency, Indonesia. The study was conducted from April to May 2025 in three maize-growing villages, namely Mulyonegoro, Puncak, and Molalahu. Soil samples were collected using a diagonal sampling technique at a depth of 0–30 cm. Soil physical properties analyzed included texture, bulk density, and water content, while chemical properties comprised soil pH, organic carbon, total nitrogen, available phosphorus (Olsen P₂O₅), exchangeable potassium, cation exchange capacity, and base saturation. The results indicated that soils in the study area were generally slightly acidic, with low organic carbon, low available phosphorus, and low base saturation, despite moderate nitrogen and high potassium availability. These conditions indicate that low organic matter content and phosphorus deficiency are the main limiting factors for soil fertility in the maize fields of Pulubala District. Integrated soil management practices, including organic matter application and balanced fertilization, are required to improve soil quality and support sustainable maize production.